2018
DOI: 10.2147/cmar.s185789
|View full text |Cite
|
Sign up to set email alerts
|

miR-424 targets AKT3 and PSAT1 and has a tumor-suppressive role in human colorectal cancer

Abstract: BackgroundRecent advances in cancer biology have uncovered critical roles for microRNAs in regulating tumor responses. This study is to elucidate the role of miR-424 in colorectal cancer development.Materials and methodsmiR-424 expression was analyzed by qRT-PCR. The role of miR-424 was studied in cell lines and animal models. The downstream targets of miR-424 were determined by microarray analysis.ResultsWe found that miR-424 expression was downregulated in human colorectal cancer cell lines and patient biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…An underlying mechanism that explains how overexpression of the PSAT1 gene contributes to a favorable outcome in LGG patients remains unclear. A number of studies have suggested overexpression of PSAT1 protein as a poor prognostic marker in colorectal cancer [17], esophageal squamous cell carcinoma [15], NSCLC [14] and ER(−) breast cancer [16]. However, a recent study suggested that a high level of PSAT1 protein could be a favorable prognostic marker for regorafenib-induced GBM suppression [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An underlying mechanism that explains how overexpression of the PSAT1 gene contributes to a favorable outcome in LGG patients remains unclear. A number of studies have suggested overexpression of PSAT1 protein as a poor prognostic marker in colorectal cancer [17], esophageal squamous cell carcinoma [15], NSCLC [14] and ER(−) breast cancer [16]. However, a recent study suggested that a high level of PSAT1 protein could be a favorable prognostic marker for regorafenib-induced GBM suppression [18].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of PSPH was found in hepatocellular cancer [12] and colorectal cancer [13]. PSAT1 mediates carbon metabolism and the TCA cycle, which provides energy and increases biomass in non-small cell lung cancer (NSCLC) [14], breast cancer [16] and colorectal cancer [17]. However, the prognostic roles of these three genes in LGGs are still unknown.…”
Section: Phgdh Psph and Psat1 Are Important Regulators Of The Ssp Amentioning
confidence: 99%
See 1 more Smart Citation
“…Hsa-mir-424 was recognized to play a dual role in various cancers. In colorectal cancer, hsa-mir-424 was identified as a tumor suppressor by suppressing cancer cell growth and enhancing apoptosis (Fang et al 2018). In addition, hsa-mir-424 was upregulated and correlated with poor survival in esophageal squamous cell carcinoma, it can promote cell proliferation by multilayered regulation of cell cycle (Wen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…miR-424-5p is a carcinogen in colorectal cancer (CRC) that directly promotes proliferation and metastasis by targeting SCN4B, CCNE1, AKT3, and Rictor. [45][46][47][48] In the field of hepatobiliary carcinoma, it has been found that miR-424-5p can inhibit the metastasis and invasion of intrahepatic cholangiocarcinoma by targeting ARK5. Moreover, in liver cancer, miR-424 can inhibit the proliferation and invasion of tumors by targeting TRIM29, YAP1, and c-Myb, while miR-424-5p can also target ICAT and inhibit tumor progression by reversing the EMT process of primary liver cancer.…”
Section: Multiplication Invasion and Migrationmentioning
confidence: 99%